Distributed Augmented Reality With 3-D Lung Dynamics?A Planning Tool Concept. - Hamza-Lup, F.G.
Augmented reality (AR) systems add visual information to the world by using advanced display techniques. The advances in miniaturization and reduced hardware costs make some of these systems feasible for applications in a wide set of fields. We present a potential component of the cyber infrastructure for the operating room of the future: a distributed AR-based software-hardware system that allows real-time visualization of three-dimensional (3-D) lung dynamics superimposed directly on the patient's body. Several emergency events (e.g., closed and tension pneumothorax) and surgical procedures related to lung (e.g., lung transplantation, lung volume reduction surgery, surgical treatment of lung infections, lung cancer surgery) could benefit from the proposed prototype
Keywords: 3-D lung dynamics; Advanced display technique; Augmented reality based visualization; Cyber infrastructure; Deformable lung models; Distributed AR-based software-hardware system; Distributed augmented virtual reality system; Lung cancer surgery; Lung infections; Lung transplantation; Lung volume reduction; Optical tracking system; Planning tool concept; Pneumothorax